2020
DOI: 10.1016/j.renene.2020.01.135
|View full text |Cite
|
Sign up to set email alerts
|

An experimental assessment of analytical blockage corrections for turbines

Abstract: In laboratory experiments involving wind or water turbines, it is often desirable to correct measured performance for the effects of model blockage. However, there has been limited experimental validation of the analytical blockage corrections presented in the literature. Therefore, the objective of this study is to evaluate corrections against experimental data and recommend one or more for future use. For this investigation, we tested a crossflow turbine and an axial-flow turbine under conditions of varying … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 38 publications
3
48
0
Order By: Relevance
“…In addition, thrust coefficient values for this turbine often exceeded unity during the tests and so no blockage Glauert (1935), but discussed in many other works (see e.g. Bahaj, Molland, Chaplin, & Batten, 2007;Chen & Liou, 2011;Mikkelsen, 2004;Ross & Polagye, 2020). However, in all tests the low-geometric blockage of the turbine was kept constant to minimize any resulting blockage effects.…”
Section: Vertical-axis Wind Turbine Modelmentioning
confidence: 84%
“…In addition, thrust coefficient values for this turbine often exceeded unity during the tests and so no blockage Glauert (1935), but discussed in many other works (see e.g. Bahaj, Molland, Chaplin, & Batten, 2007;Chen & Liou, 2011;Mikkelsen, 2004;Ross & Polagye, 2020). However, in all tests the low-geometric blockage of the turbine was kept constant to minimize any resulting blockage effects.…”
Section: Vertical-axis Wind Turbine Modelmentioning
confidence: 84%
“…The blockage correction presented by Maskell (1965) is not valid for porous bodies, as it assumes zero wake velocities, while various corrective models based on actuator disks (Bahaj et al 2007; Werle 2010), often used in wind engineering, are not valid for cases where the bluff-body porosity is small. A recent review of blockage correction models can be found in Ross & Polagye (2020). Although blockage will affect the magnitude of the drag coefficients, care was taken such that it would not alter the trends or the conclusions of the study.…”
Section: Methodsmentioning
confidence: 99%
“…Later in the decade, tow tank experiments were conducted by Wosnik group for a reference cross-flow hydrokinetic turbine [6,7]. Related to this reference model, Ross and Polagye performed various experimental measurements with other smaller scaled turbine models to assess analytically models of blockage effect on cross-flow turbines [8]. Other than tow tank experiments, studies of small scaled turbines in water flumes have also been fruitful for the community.…”
Section: Introductionmentioning
confidence: 99%